If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c(c + -8) = 0 Reorder the terms: 2c(-8 + c) = 0 (-8 * 2c + c * 2c) = 0 (-16c + 2c2) = 0 Solving -16c + 2c2 = 0 Solving for variable 'c'. Factor out the Greatest Common Factor (GCF), '2c'. 2c(-8 + c) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-8 + c)' equal to zero and attempt to solve: Simplifying -8 + c = 0 Solving -8 + c = 0 Move all terms containing c to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + c = 0 + 8 Combine like terms: -8 + 8 = 0 0 + c = 0 + 8 c = 0 + 8 Combine like terms: 0 + 8 = 8 c = 8 Simplifying c = 8Solution
c = {0, 8}
| 7+4x+5x=-92 | | -5(b+4)-6b=24 | | 1+3n-4n=3n-11 | | 28000+3000n=36000+2000n | | 4x^2y^2+12xy+9= | | 2x+4=10x-36 | | -9-7b=8b-7 | | 1+c/8=c/4 | | 4x^2y^2+12xy+9=0 | | -5(m+9)-4+8m= | | 6+4q=7+3g | | 1/6-2/3x=1/12 | | 5x+4-7x=8+2x | | 7/12x9 | | 16n=432 | | -7y-1=6y-6 | | 5x-8=30x+7 | | -7x+3=2x+-1 | | 9r+2=65 | | -31-(-8.6)= | | 18-3.8t=7.36-1.96 | | 5(2x+5)=-35+30 | | 6m-1=5m-2 | | 2a+b=15.7 | | 18-3.8t=7.36-1.98 | | -3-4x=-5x | | (2k-4)x+(4k+6)y+(3q-2)=0 | | 3x-2.8=4.2-4x | | 9x+6x+4=114 | | 37=5 | | (2k-x)x+(4k+6)y+(3q-2)=0 | | 15.3-(-11)= |